EVALUASI PENATAAN NEGARA DALAM INSTRUMEN PENANGGULANGAN PERUBAHAN IKLIM (PERSPEKTIF HUKUM DAN EKONOMI) - Bram, Deni (Global: Jurnal Politik Internasional, 2011)
Compliance is a spirit in a law enforcement system. Precise rules and sanctions are defined in detail is sometimes not able enough to be reason and affects the rationality of the stipulated legal subjects. Law and Economic approach try to carry the economy instrument in a comprehensive assessment in order to optimize compliance with the rules. This article tries to give the perspective of economic analysis of law in the realm of international treaties in the field of climate change, sanctions that are too lightweight and low cost that must be done as a follow disobedience became the main focus in this paper that tried to look in the calculation of cost benefit analysis